2022
DOI: 10.1038/s41557-021-00880-2
|View full text |Cite
|
Sign up to set email alerts
|

Fast CO2 hydration kinetics impair heterogeneous but improve enzymatic CO2 reduction catalysis

Abstract: The performance of heterogeneous catalysts for electrocatalytic CO 2 reduction (CO 2 R) suffers from unwanted side reactions and kinetic inefficiencies at the required large overpotential. However, immobilised CO 2 R enzymes — such as formate dehydrogenase — can operate with high turnover and selectivity at a minimal overpotential and are therefore ‘ideal’ model catalysts. Here, through the co-immobilisation of carbonic anhydrase, we study th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 52 publications
1
59
0
Order By: Relevance
“…While we have previously shown that FDh produces formate with nearly 100% FE under pure CO2 on ITO, 28,38 the reduced FE under low CO2 concentrations can be tentatively attributed to the residual background reduction of the metal oxide electrode. [39][40][41] This can be observed in the absence of enzymes with no liquid or gaseous products being detected by Ion or Gas Chromatography, respectively (Figure S5) at current densities that match well with the unattributed FE under low CO2 concentrations.…”
Section: Bicarbonate As a Semi-artificial Carboxysome Electrolytementioning
confidence: 80%
See 3 more Smart Citations
“…While we have previously shown that FDh produces formate with nearly 100% FE under pure CO2 on ITO, 28,38 the reduced FE under low CO2 concentrations can be tentatively attributed to the residual background reduction of the metal oxide electrode. [39][40][41] This can be observed in the absence of enzymes with no liquid or gaseous products being detected by Ion or Gas Chromatography, respectively (Figure S5) at current densities that match well with the unattributed FE under low CO2 concentrations.…”
Section: Bicarbonate As a Semi-artificial Carboxysome Electrolytementioning
confidence: 80%
“…The formate partial current density of CO2R by immobilized FDh (jformate, points, Figure 2a) in 1% and 10% CO2 purged solutions with N2 as the balance gas, unlike when purged with concentrated CO2 28 , was not affected by CA co-immobilization. Formate was the quantitative product as no other liquid or gas phase products (such as H2, CO or CH4) were detected by ion chromatography or headspace gas chromatography, respectively (for total and partial current densities from all experiments including controls see Table S2).…”
Section: Bicarbonate As a Semi-artificial Carboxysome Electrolytementioning
confidence: 99%
See 2 more Smart Citations
“…Taken together, in situ ATR FTIR difference spectroscopy allowed investigating the interaction of different enzymes with CO2, providing a simple, yet powerful approach to directly identify CA activity for a given biological sample. Moreover, our method is also suited to identify and characterize the source of water and will serve as an important tool to analyze CO2 hydration in biocatalysis [28][29][30][31] , homogenous or heterogeneous catalysts [32][33][34] , and (de-)hydration reactions in general. [35,36]…”
Section: Discussionmentioning
confidence: 99%